Ketotic Hypoglycemia in Children: A Review - Mridha, Md Al Amin; Matin, Abdul (Bangladesh Journal of Child Health, 2019)
Ketotic hypoglycemia is the most common form of childhood hypoglycemia. Hypoglycemic episodes typically occur during periods of intercurrent illness when food intake is limited. The term ketosis should not be confused with Ketoacidosis. Children with ketotic hypoglycemia have plasma alanine concentrations that are markedly reduced in the basal state after an overnight fast and decline even further with prolonged fasting. The classic history is of a child who has eaten poorly or misses an evening meal, is difficult to rouse from sleep the next morning, and displays neuroglycopenic symptoms that may range from lethargy to seizure. Hypoglycemic episodes are especially likely to occur during an illness, when food intake is limited. Clinical diagnosis is made by identification of ketones in plasma and urine, Whipple’s triad hypoglycemia, and exclusion of endocrine/metabolic disease. It is therefore essential that appropriate investigation is performed at the time of hypoglycemia to exclude other causes This condition usually presents between the ages of 18 months to 5 years and it commonly remits spontaneously by the age of 8 to 9 years. Bangladesh J Child Health 2019; VOL 43 (2) :113-116